2019
DOI: 10.1093/eurpub/ckz131
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic medication before and after disability retirement by pre-retirement perceived work-related stress

Abstract: Background Retirement has been associated with improved mental health, but it is unclear how much this is due to the removal of work-related stressors. We examined rates of psychotropic medication use before and after the transition to disability retirement due to mental, musculoskeletal and other causes by pre-retirement levels of perceived work stress (effort-reward imbalance, ERI). Methods Register-based date and diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that mental strain and psychological symptoms often tend to alleviate after retirement. 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that mental strain and psychological symptoms often tend to alleviate after retirement. 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
“…Patients with a long remission period were likely to have been prescribed conventional psychotropic drugs because their symptoms subsided and a longer remission was associated with fewer prescribed psychotropic drugs and lower dosage. In addition, job-related stress which often aggravates psychopathological symptoms, decreases after retirement [ 27 ]. The dosage of prescribed psychotropic drugs can be reduced in the elderly to avoid adverse physical effects, [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the decline in purchases may reflect an absence of work-related strains or fewer attempts to restore work ability. In deed, Halonen et al [36] have shown that for mental health-based disability retirees, the pre-retirement level of psychotropic drug purchases can depend on perceived preretirement work stress, while this effect attenuates after retirement. Laaksonen et al [10] respectively assume that the increase in psychotropic drug consumption among disability retirees reflects the fact that health care and pension systems identify those with disabling health problems.…”
Section: Discussionmentioning
confidence: 99%
“…For many, the decreasing amount of drug consumption probably reflects improving mental health. For awarded applicants, this may be due to reduced stress and absence of work-related strains [36,45]. For some of the awarded applicants, lowering drug purchase levels could in contrast reflect a decreasing incentive to improve functional capacity once the pension benefit is reached.…”
Section: Awarded and Rejected Applicants After The Pension Decisionmentioning
confidence: 99%